DIABETIC KETOACIDOSIS IN CHILDREN AND ADOLESCENTS WITH TYPE 1 DIABETES MELLITUS AND ASSOCIATED RISK FACTORS - Thaynara Tavares Oliveira Ramos; Juliana Andreia Fernandes Noronha; Brenda Sales Lins; Maria Cecília Queiroga dos Santos; Sheila Milena Pessoa dos Santos; Anajás da Silva Cardoso Cantalice (Cogitare Enfermagem, 2022)
Objective: to estimate the prevalence and risk factors of diabetic ketoacidosis in children and adolescents with Type 1 Diabetes Mellitus.